A Case of Lung Volume Reduction Surgery in a Young Adult With Chronic Lung Disease - Horinouchi, Hirohisa; Maitani, Fumio; Miyauchi, Jun (Respirology case reports, 2025)
ABSTRACT Chronic lung disease, characterised by impaired development and/or fibrotic changes in the lungs of preterm neonates, results in lifelong consequences that affect respiratory well‐being. An 18‐year‐old male with chronic lung disease presented with shortness of breath upon exertion. Computed tomography revealed bilateral emphysema and a large bulla in the left lower lobe. Additionally, severe obstructive ventilatory impairment was observed and respiratory rehabilitation was ineffective in improving lung function. We performed lung volume reduction surgery on the left lower lobe, resulting in improved ventilatory function and exercise capability. This case shows that emphysematous changes in patients with chronic lung disease can be successfully treated with surgery. An 18‐year‐old boy with chronic lung disease reported experiencing shortness of breath during exertion for the past year. He was diagnosed with severe emphysema, along with a giant bulla in his left lower lobe. Treatment with bronchodilators and respiratory rehabilitation did not alleviate his symptoms. Consequently, he underwent lung volume reduction surgery on his left lower lobe. Following the procedure, his ventilatory function improved, and his symptoms were significantly reduced.